Associations of maternal insulin resistance during pregnancy and offspring inflammation at birth and at 5 years of age: A prospective study in the Gen3G cohort. (October 2021) - Faleschini, Sabrina; Doyon, Myriam; Arguin, Mélina; Perron, Patrice; Bouchard, Luigi; Hivert, Marie-France
Highlights: Greater gestational insulin resistance was associated with lower TNFα levels at birth. No association between maternal glucose levels and offspring TNFα was found. No association between insulin resistance and child TNFα was found at 5 years of age. Abstract: Background: Maternal insulin resistance is associated with greater maternal inflammation during pregnancy, but its relation to inflammation in offspring remains unclear. The goal of this study was to assess the relationship of gestational insulin resistance and other glycemic markers with offspring inflammation at birth and at 5 years of age. Methods: We included 653 mother–child pairs from the prospective pre-birth Gen3G cohort. We examined maternal insulin and glucose levels measured during the second trimester of pregnancy, from which we derived the homeostatic model of assessment of insulin resistance (HOMA-IR) and the Matsuda index. We assessed offspring inflammation at birth and at 5 years of age by measuring plasma tumor necrosis factor-α (TNFα) concentrations. We conducted multivariable regression models to evaluate associations of each insulin and glucose marker with offspring inflammation adjusting for confounding variables. Results: Higher levels of fasting insulin were associated with lower TNFα levels at birth (−0.78, 95% CI [−1.45, −0.11]), in the fully adjusted model. We observed similar associations with the HOMA-IR and opposite direction with the Matsuda index. We did not find persistence of the association between maternal fasting insulin and offspring TNFα at 5 years of age. Conclusions: Greater maternal insulin resistance during pregnancy was associated with lower cord blood TNFα levels in newborns. The mechanisms by which maternal insulin resistance may promote lower inflammatory levels in newborns are not fully understood and more research is needed to deepen our understanding of these mechanisms.